السلوكات الإستراتجية للمؤسسة تجاه المسؤولية الاجتماعية - دراسة حالة الجزائرية القطرية للصلب - - كريد, فيصل (جامعة الوادي - University of Eloued, 2024)
This study aims to determine the position of the Algerian company’s strategic behaviors towards corporate sociale responsibility (CSR). To achieve this objective, we have tried to collect those behaviors based on the most relevant authors’ contributions, and then, we have gathered them into three levels, to analyse the engagement of Algerian Qatari steel (AQS) in social and environmental dimensions. In the end, we have concluded that the group generally swings between two levels: Implicit strategy, wherein the performance does not go beyond mandatory requirements, and explicit strategy, through which the performance overtakes normative references. We have advanced also some recommendations to improve the status quo of the company, in order to avoid social pressures, such as using objective standards, and adopting the KPIs issued by the World Steel Association (WSA).
Company’s strategic behaviors towords corporate social responsability -Case study of Algerian Qatari Steel (AQS) –
مقال
Keywords: المسؤولية الاجتماعية للمؤسسة ; إستراتيجية ضمنية ; إستراتيجية صرحية ; تقييم الأداء; CSR, implicit strategy, explicit startegy, performance evaluation